Zjawisko ukrytej przemocy wobec najmłodszych uczniów na zajęciach matematycznych - Alina Kalinowska (Problemy Wczesnej Edukacji)
The paper undertakes research meant to identify the teacher’s violent behaviour towards students during early school math lessons. The research conducted in grade one during the math class was used as an aid to deeper understanding of the phenomenon of violence in school. It was found that some lesson procedures, mathematical formulations, and cognitive situations can be seen from the perspective of teacher violence. Their effects can reduce pupils’ self-esteem, limit understanding of mathematics and hinder full participation in culture now and in the future.